THEORETICAL AND METHODOLOGICAL APPROACHES TO INTERPRETATION OF THE CONCEPT «INTENSIFICATION OF STUDENTS` STUDY AND COGNITIVE ACTIVITY» : HISTORICAL AND PEDAGOGICAL ASPECT - Світлана Виговська; Вікторія Пабат (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article deals with the essence of the concept of "intensification of students' study and cognitive activity", methodological approaches to its treatment. It has been clarified, that a didactic and methodological approach lies in the development of organizational and practical forms of involvement of subjects of study into active cognitive activity. Authors' main attention is focused on teacher's activity on engaging students in cognitive process. In the cognitive approach the subject of study is the creative activity of the subjects of study and its active nature. The attention of researchers is also paid to the process of cognition through activization of a personality's activity. The integrative approach involves simultaneous consideration of the concept of "intensification of study and cognitive activity " from the side of a teacher's activity, and the term "active cognitive activity "is treated as the activity of a student in the didactic process.